Effect of chewing gum on stress and mood among UiTM student / Nur Sakinatul Husna Ramli - Ramli, Nur Sakinatul Husna (2018)
Previous research suggested that chewing gum intake may improve of stress and mood. The effects of chewing gum on psychological stress and mood were also still controversial and inconsistent. Therefore, it is important to examine the effectiveness of chewing gum intake. The aims of the present study to determine the effect of chewing gum on stress and ·mood among UiTM student. Stress is that it is an organic reaction to a physiological or _mental. Stress can be activated by mental and physical stress. Considering that chewing has beneficial effect on the stress levels and mood, the aim of this study is to find whether chewing gum is effective in reducing stress and mood among UiTM student. An experimental research design involving forty (N=40) UiTM student male and female from FSKM and FSR was carried out. Each participant was selected using conveniently incidental selected sampling technique. All of the participants were tested in the same environment which is with normal temperature 22°. Participants were reassured on stress and mood states. The experimental procedure consists of two part which is pre and post intervention. Firstly, the participants would rate their stress and mood during pre intervention. The stress and mood were rated with questionnaires. The questionnaires are The Perceived Stress Scale (PSS-10) and Brunel Mood Scale (BRUMS). Then, the participants would be given chewing gum chewing gum to chew for IO minutes. Lastly, post measurement was taken. Significant effect of chewing gum on stress <0.05 then there is significant effect of chewing gum on mood in several mood scale ( calmness, fatigue, confusion & happy). There is no significant effect on anger, vigour, tension and depression. In conclusion, IO minutes chewing gum intake is sufficient to regulate stress and mood state.